Chemical Constituents from the Rice Straw of Oryza sativa - Ahmad, Ateeque; Yoon, Jae-Yeon; Chung, Ill-Min (Asian Journal of Chemistry, 2013)
Four compounds, n-hexacosanyl palmitate (1), n-hexacosanyl oleate (2), n-nonacosanyl linoleiate (3) and stigmasterol (4) were isolated from the methanol extract of Oryza sativa of rice straw. The structures of the compounds were elucidated using 1H NMR, 13C NMR in combination with IR, ESI/MS, ESI/FTMS.